Herbal Plants for Lowering Blood Pressure in Hypertension Patients at UPTD WKJ Tegal - Anwar Sodik; Ayu Nissa Ainni; Titi Pudji Rahayu; Laeli Fitriati; Safitri, Safitri (Jurnal EduHealth, 2025)
Hypertension is a major risk factor for cardiovascular diseases, including atherosclerosis, heart failure, kidney failure, and stroke. The long-term use of chemical medications poses the risk of side effects that may damage certain organ functions. Thus, alternative therapies are needed to reduce dependence on medication and help maintain the quality of life of hypertensive patients. One alternative treatment that can be considered for lowering blood pressure is herbal therapy. The herbal plants examined in this literature study are Orthosiphon aristatus and celery. Orthosiphon aristatus contains apigenin compounds that act as diuretics, while celery contains flavonoids that work by dilating blood vessels, allowing blood to flow more freely and thereby reducing blood pressure. Research objective to identify herbal plants and their active compounds used as hypertension therapy based on prescriptions at UPTD WKJ Tegal. The research method used is a literature study developed based on prescriptions for hypertension patients at UPTD WKJ Tegal. According to the journal findings on celery leaves, the difference in blood pressure before and after administration of celery leaf decoction was measured. The average difference (mean) in diastolic blood pressure was 11.33 mmHg, and the difference in systolic blood pressure was 8.67 mmHg. This indicates a significant reduction in blood pressure after administering celery leaf decoction for five consecutive days. In the study on Orthosiphon aristatus leaves, the frequency of urination in elderly patients before administration of Orthosiphon aristatus infusion was 3.00 times (range 2–6). After administering the infusion once daily for seven consecutive days, the frequency increased to 6.00 times (range 3–9), with an average difference of 2.2 times in urination frequency. This demonstrates that the infusion of Orthosiphon aristatus leaves has a diuretic effect on elderly hypertensive patients. Celery (Apium graveolens) and Orthosiphon aristatus herbal plants have been shown to effectively reduce blood pressure in patients with hypertension